A Mixed-Methods Pilot Study of Mindfulness-Based Stress Reduction for HIV-Associated Chronic Pain. Issue 2 (3rd April 2017) - George, Mary Catherine; Wongmek, Arada; Kaku, Michelle; Nmashie, Alexandra; Robinson-Papp, Jessica
ABSTRACT: Treatment guidelines for chronic pain recommend nonpharmacologic modalities as part of a comprehensive management plan. Chronic pain is common among people living with HIV/AIDS, but there is little data to guide the choice of nonpharmacologic therapies in this complex population. We performed a mixed-methods feasibility study of Mindfulness-Based Stress Reduction (MBSR) versus health education control with 32 inner city, HIV-infected participants. Outcome measures included: the Brief Pain Inventory, Perceived Stress Scale, HIV Symptoms Index, autonomic function testing, and audiotaped focus groups. Post-intervention, participants reported modest improvements in pain measures and perceived stress, but no effect of group assignment was observed. At 3-month follow-up, 79% of MBSR participants were still practicing, and pain intensity was improved, whereas in the control group pain intensity had worsened. Qualitative analysis revealed a strong sense of community in both groups, but only MBSR was perceived as useful for relaxation and pain relief.